2015
DOI: 10.1002/2015ja021160
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of ions by electric field pulses in the inner magnetosphere

Abstract: Intense (∼5–15 mV/m), short‐lived (≤1 min) electric field pulses have been observed to accompany earthward propagating, dipolarizing flux bundles (flux tubes with a strong magnetic field) before they are stopped by the strong dipole field. Using Time History of Events and Macroscale Interactions during Substorms observations and test particle modeling, we investigate particle acceleration around L shell ∼7–9 in the nightside magnetosphere and demonstrate that such pulses can effectively accelerate ions with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 67 publications
5
37
0
Order By: Relevance
“…The electric field magnitude is typically 3 times greater for the former than for the latter. This supports previous models suggesting that injections result from a DFB's electric field directly accelerating or ushering particles into the inner magnetosphere Gabrielse et al, 2012;Birn et al, 2013;Artemyev et al, 2015]. Consistent with their electric field difference, DFBs with injection move faster than DFBs without.…”
Section: Summary and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The electric field magnitude is typically 3 times greater for the former than for the latter. This supports previous models suggesting that injections result from a DFB's electric field directly accelerating or ushering particles into the inner magnetosphere Gabrielse et al, 2012;Birn et al, 2013;Artemyev et al, 2015]. Consistent with their electric field difference, DFBs with injection move faster than DFBs without.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…(Note that our electric fields are smaller than the values of Artemyev et al . [] because ours are averages over 1 min. The peaks of our electric fields are up to 42 mV/m.)…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Multiple models have been proposed to explain observations of energetic particle injections (e.g., Artemyev et al, 2015;Birn et al, 1998;Gabrielse et al, 2012Gabrielse et al, , 2016Gabrielse et al, 2017;Li et al, 1998;Li et al, 2003;Mauk & McIlwain, 1974;Reeves et al, 1991;Sarris et al, 2002;Ukhorskiy et al, 2017). Previous studies (e.g., Angelopoulos et al, 2008;Baker et al, 1996) suggest that some energetic particle injections result from earthward moving plasma (e.g., plasma bubbles or dipolarizing flux bundles) associated with a sharp enhancement in the z component of the magnetic field (i.e., dipolarization or dipolarization front).…”
Section: Introductionmentioning
confidence: 99%
“…Such enhancements result most likely from particle acceleration by DFBs. This acceleration can be either adiabatic (Ashour‐Abdalla et al, ; Deng et al, ; Fu et al, ; Runov et al, ), most simply understood as caused by the electric field accompanying moving DFBs (e.g., Artemyev et al, ; Gabrielse et al, ; Zhou et al, ), or nonadiabatic due to large amplitude waves observed in the DFB vicinity (Zhou et al, ). For some DFBs that can penetrate into the inner magnetosphere, the electric field related to the DFB evolution can still be large and lead to significant local particle acceleration (Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%